Nouvelles dédicaces d’Alésia à Apollon Moritasgus - Olivier de Cazanove; Monique Dondin-Payre (Gallia)
Three new dedications to Apollo Moritasgus are published here which belong to the god’s sanctuary on the eastern edge of Alesia. The first one comes from Espérandieu’s old excavations, in 1910. A recent restoration revealed an inscription on a bronze sheet representing eyes. The dedication is made by the peregrine Sabinnus. The other dedications two come from recent excavations in the same sanctuary and are engraved on the handles of bronze paterae or pans. The first one (found in 2011, in a manhole of a water channel, right north of the temple) bears the dedication by a Roman citizen whose sole cognomen, Iullinus, is preserved, who fulfills a vow granted by his sister Fuscina. The second one was found in 2013 next to the rear wall of a great porticus with paraskenia, in a well-defined chronological context (last third of 1st, first half of 2nd century AD). Veio, son of Natalis, who made the dedication, is a peregrine. A last inscription, known since 1909 (Espérandieu’s excavations of a secondary spring catchment), on a metallescent ceramic handle, makes it possible to increase this small series of similar objects, well attested in spring sanctuaries. One can therefore suggest that the three paterae bearing dedications, from the sanctuary of Apollo Moritasgus, had an identical practical and ritual use, before being gathered together with the other offerings exposed in the sanctuary.